Вбрання Констанція II на верхівнянському медальйоні - Гороховський, Є.Л.; Корнієнко, П.Л. (Археологія, 1993)
У публікації аналізується вбрання римського імператора Констанція II (337-361 рр. н. е.), зображене на золотому медальйоні. Золотой позднеримский медальон императора Констанция II (337—361 гг.), происходящий из с. Верховня Ружинского района Житомирской области, принадлежит к выдающимся археолого-нумизматическим памятникам Европы, обнаруженным в последние годы. По мнению исследователей (Б. Б. Гарбуз, С. А. Яценко), он чеканен в 358 г. в ознаменование победы Рима над потисскими сарматами-лимигантами в войне 357—358 гг. Медальон содержит изображения: императора-триумфатора в полный рост на реверсе и его бюста на аверсе. Победитель облачен в парадное воинское одеяние. Исследование состава и компонентов последнего, составляющее основное содержание статьи, осуществлено с привлечением обширного сравнительного материала: нумизматического и изобразительного, содержащего иконографию одежды и вооружения римско-византийского и восточного происхождения, а также вещественных археологических и письменных источников. Golden late-Roman medallion of emperor Constandum the Second (337—361) originated from vil, Verkhovnya (Ruzhin District, Zhitomir Region) belongs to remarkable archaeological-numismatic relics of Europe found for last years. The researchers (В. B. Garbuz, S. A. Yatsenko) think it to be stamped in 358 to mark the Rome victory over Potissian Sarmatians-Limigants in war of 357—358. The medallion depicts the triumpher-emperor standing up straight on a reverse and its bust on an averse. The conqueror is garbed in a smart military uniform. The study of the composition and a complete set of the uniform is the main purpose of the presented paper. It was done using vast comparative numismatic and graphic materials containing iconography of garments and arms of the Roman-Byzantine and Oriental origin, material archaeological and written sources. Stylistic attributes characterizing depiction of certain details of the emperor's garments on the medallion and its structure as a whole are typical of fine arts of the Late Roman Empire of the period when the early Byzantine culture was formed (the 4th cent. A. D.), The integrally unite archaeological canons formed in iconography of Julius Caesar and sovereigns of early- empire Pome (images in metal armours like «muscular cuirass» according to H. Robinson, sandals) and new canons mainly of the Oriental origin. The latter include a custom to depict a sovereign crowned with a «jewellery» (by R. Delbruek), gem-encrusted diadem, in garments cut of precious coloured fabrics decorated with jewels, gorgeous embroidery and applique. An example of the peculiar «syncretism» is a typical Roman cloak, a paludamentum with applique fastened by a splendid broach encrusted with a gem. All those attributes go back to fashions of the former Hellinistic states which become Roman provinces (Greece, Syria, Egypt, Asia Minor) and, partially to Parphian and Sasanidian fashions. So, attire of Constancium the Second depicted on a medallion reflects both the roman traditions and Oriental innovations that intensively permiated material culture of the Empire parallel with «Oriental» cults, philosophy and other «influences» which spreaded as long ago as in the republican period. At the epoch of a dominat the «orientalization» of Roman culture looks like already formed phenomenon which is vividly exhibited in iconography of garments. The period of the highest intensification of this phenomena had begun as far back as with Severs who stimulated the «orientalization» process from above, which is confirmed by written sources and by certain depictions of representatives of that dynasty in painting and glass. The process of the material culture «orientalization» in Empire Rome is also tightly connected with a rise and development of Early-Christian culture which in total with the heritage of «classical» Greek-Roman and Oriental-Hellinistic traditions has underlain the early Byzantium phenomenon.